Here's the question you clicked on:
andriod09
(x-4)(x-(1/4))(x+10)=(log(pi)+sin(pi/7)^0-1
So it looks pretty complicated, but if you take a look at the right side you see that the complex pi/log/sin stuff is all raised to the 0th power, which means it's 1 (ANYTHING raised to the 0th power is 1). So if we replace that by 1 we get \[ (x-4)(x-\frac{1}{4})(x+10)=1-1=0 \] Now it should be pretty easy.
I CANNOT SEE EQUATIONS FRO MTHE EQUATION BUTTON!!! ALL I SEE ARE THE SLASHES AND THE BRACKETS AND THE BRACES!!
Okay, what I wrote was: (x-4)(x-1/4)(x+10)=1-1=0
and also, i kthe answer, i was wondering how many others can get it.